Concept of Biohydrogen Production by Agricultural Enterprises (Agricultural Engineering, 2021)
Biohydrogen production in agricultural enterprises is an urgent matter. It is appropriate to utilize two methods of biohydrogen production: a thermochemical method – from crop-based biomass and anaerobic digestion (fermentation) method – from animal-based biomass.. It is appropriate to use gasifiers for the thermochemical method and biore-actors for fermentation method.The theoretical potential of biohydrogen was established with due regard to the amount of biomass which is necessary for utilization in livestock agriculture, for fields fertilization as well as with the consideration of the coefficients of concordance with hydrogen equivalent and loss factor under biohydrogen production. The theoretical potential of biohydrogen from crop-based biomass in Ukraine amounts to 77 billion m3, during the period of three years (on average 25.6 billion m3 per year).